Acrylamide Neurotoxicity Studies in Caenorhabditis elegans Model - Zhonglian Ma; Liang Ma; Yuhao Zhang (Antioxidants)
Acrylamide (ACR), utilized as a precursor for producing polyacrylamide for water purification, has demonstrated neurotoxic properties. However, the mechanisms underlying its neurotoxicity remain inadequately understood. In this investigation, Caenorhabditis elegans were exposed to ACR at concentrations ranging from 250 to 1000 μg/mL and then their locomotor behavior, neuronal development, neurotransmitter concentrations, and gene expression profiles were assessed. Exposure to 250–1000 μg/mL ACR resulted in observable behaviors such as head swiveling and body bending, accompanied by a significant reduction in body size. Furthermore, ACR exposure caused damage to serotonergic, cholinergic, dopaminergic, and glutamatergic neuronal structures. In this context, elevated levels of serotonin, dopamine, acetylcholine, and glutamate were detected, along with notable upregulation of the expression of genes associated with neurotransmitters, including tph-1, cat-4, mod-1, mod-5, cat-1, ser-1, dat-1, dop-1, dop-3, unc-17, cho-1, eat-4, and glr-2. Moreover, ACR exposure elevated reactive oxygen species (ROS), O2, and H2O2 levels while concurrently depleting glutathione (GSH), thereby compromising the antioxidant defense system. This led to a significant upsurge in the expression of genes involved in the nematode ACR detoxification pathway, specifically daf-16, skn-1, mlt-1, sod-3, gst-4, gcs-1, hsf-1, and hsp-16.2. Additionally, Spearman correlation analysis revealed a significant inverse relationship between certain neurotransmitter and antioxidant genes and locomotor activities, highlighting the role of these genes in mediating ACR-induced neurotoxicity in C. elegans. Collectively, this research enhances the understanding of the mechanisms related to ACR neurotoxicity.